2018
DOI: 10.1016/j.rmed.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium add-on to inhaled corticosteroids versus addition of long-acting β2-agonists for adults with asthma

Abstract: Additional management options, and better use of current options, are needed to help support a large proportion of patients with asthma whose symptoms remain uncontrolled on inhaled corticosteroids (ICS). Here, we aim to review the safety and efficacy of adding tiotropium to ICS compared with adding a long-acting β-agonist (LABA) for adults whose asthma is not well controlled on ICS alone. Adding tiotropium to a background of ICS provides beneficial effects that are comparable with addition of a LABA in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Improvements in peak and trough FEV 1 were observed with 2.5 µg tiotropium Respimat ® compared with placebo in the majority of studies [1618, 20, 21, 27, 29]. Although the minimal clinically important difference for FEV 1 responses in patients with asthma is not well defined, the observed effect sizes in this analysis were comparable to those observed with the addition of LABA to ICS therapy [20, 3032]. Our findings show that 2.5 µg tiotropium Respimat ® improved FVC in patients with moderate asthma (adults and children aged 6–11 years), providing a good measure of potential effects of tiotropium on small-airway dysfunction [33].…”
Section: Discussionsupporting
confidence: 61%
“…Improvements in peak and trough FEV 1 were observed with 2.5 µg tiotropium Respimat ® compared with placebo in the majority of studies [1618, 20, 21, 27, 29]. Although the minimal clinically important difference for FEV 1 responses in patients with asthma is not well defined, the observed effect sizes in this analysis were comparable to those observed with the addition of LABA to ICS therapy [20, 3032]. Our findings show that 2.5 µg tiotropium Respimat ® improved FVC in patients with moderate asthma (adults and children aged 6–11 years), providing a good measure of potential effects of tiotropium on small-airway dysfunction [33].…”
Section: Discussionsupporting
confidence: 61%
“…14 Furthermore, the use of a LAMA, either in addition to LABA + ICS or as an alternative to a LABA added to ICS maintenance therapy, may be needed as add-on treatment in patients whose asthma is not well controlled on ICS and LABA. 15,16 Of note, patients with severe asthma are good candidates for treatment with anti-inflammatory therapies, including newer biologic agents that target T-helper type 2 (Th2)–driven inflammatory pathways, because Th2-type inflammation is more common in these patients. 17 Add-on therapy with immunomodulators, used in specific asthma populations having a severe asthma phenotype, has been shown to reduce exacerbations 18,19 and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent reviews of tiotropium outcome trials demonstrated positive evidence for the benefits of tiotropium use in asthma across adults, children, and patients with heterogeneous asthma (phenotypes and endotypes) profiles 1415. For step 5 treatment, tiotropium has been shown to be beneficial16 and more cost-effective 14. Overall, tiotropium may be a preferred choice considering that the newer biologics therapy, that is, anti-IgE or anti-IL5, are less affordable in China in light of the lower economic status.…”
Section: Discussionmentioning
confidence: 99%